EXPLOSIVITY ANALYSIS ON COAL WITH SIZE 53 μm - 44 μm USING EXPLOSION CHAMBER SIZE 10 L ON LABORATORY SCALE - MUHAMMAD IMAM K (NIM : 12114085) , RADEN
Explosion on underground mine have cause deaths and injury to workers and damage in every country that coal being mined using underground mining method. Started from 1810 on United States of America reported that a significant number of explosion in mine caused by combination of methane, dust coal, and ignition sources. Because of lack on research about coal dust explosivity in Indonesia therefore, this kind of research is needed. On this research focused mainly to effects of coal dust size 53 μm - 44 μm if it exposed by ignition sources and will cause explosion on variety of concentration that is 100 g/𝑚3, 150 g/𝑚3, 200 g/𝑚3dan 250 g/𝑚3. These concentrations are chosen based on research that have been done before. Because on smaller concentration there is not shown any sign of explosivity. On this research use pressured air to inject coal up to 20 bar into explosion chamber where inside it there are ignition source in form of pyrotechnic with energy of 5 kJ that initiated when coal are being injected with time delay of 0.06 seconds. Required the result of this research is biggest explosion pressure, maximum rate of pressure rise, maximum energy on test code O1 that is test with concentration of 200 gr/M^3 with details consist of Pex = 15,5 bar, (dP/dt) = 629,86 bar/s, dan Maximum energy = 7,75 MJ/kg where it is equal to 1,85 kg TNT.